Electromagnetic method field test for characterizing steel fibers in ultra-high performance concrete (UHPC). (17th April 2023) - Alabi, Daniel J.; Voss, Megan; Ferraro, Christopher C.; Riding, Kyle; Harley, Joel B.
Abstract: The use of ultra-high performance concrete (UHPC) has been growing in the construction industry due to its excellent flexural, tensile, and compressive strengths. The flexural and tensile strength of UHPC is often augmented by the addition of steel fibers. However, the strength of UHPC is highly dependent on the density and orientation distribution of those fibers. Failure to properly distribute the fibers can lead to failures. As a result, steel fiber distributions need to be characterized post-fabrication. Among available testing methods, an electromagnetic technique based on induction sensing had shown significant promise. However, there has been no field experiments to verify fiber density and orientation in real UHPC fabrication. This paper studies the effectiveness of the electromagnetic technique on field-fabricated UHPC. The measurements from our electromagnetic sensor are validated from cores studied with a computed tomography (CT) scan. We demonstrate a 98% correlation between our electromagnetic method and the CT scan results for the orientation, and a root mean square error (RMSE) of 0.295% for the density of the fibers. Highlights: A field test method was setup for Ultra-high performing concrete (UHPC). Nondestructive testing of concrete using an electromagnetic sensor. Steel fiber volume and orientation quantification using electromagnetic sensor.